P.021 Evaluation of PREEMPT fixed-dose, fixed-site and follow the pain treatment paradigms in the PREDICT Study. (June 2022) - Graboski, C; Ong-Lam, M; Becker, W; Boudreau, G; Davidovic, G; Ma, J; Sommer, K; Finkelstein, I
Abstract : Background: Phase 3 PREEMPT established safety and efficacy of 155-195U onabotulinumtoxinA in adults with chronic migraine (CM). This analysis of the PREDICT study (NCT02502123) evaluates real-world effectiveness and safety of 155U, 156-195U and 195U-onabotulinumtoxinA in CM. Methods: Patients received onabotulinumtoxinA approximately every 12-weeks (≤7 treatment cycles [Tx]) per Canadian product monograph). Primary endpoint was mean change from baseline in Migraine-Specific Quality of Life (MSQ) at Tx4. Headache days, physician and patient satisfaction were evaluated. Analysis stratified safety population (≥1 onabotulinumtoxin A dose) into 3 groups (155U, 156-195U, 195U) by dose received on ≥3 of the first 4 Tx. Results: 184 patients received ≥1 onabotulinumtoxin A dose (155U, n=68; 156-195U, n=156; 195U, n=13 on ≥3 Tx). Headache days decreased over time compared to baseline (Tx4: -7.1[6.7] 155U; -6.5[6.7] 156-195U; -11.2[6.4] 195U). Physicians rated most patients as improved, and majority of patients were satisfied at final visit (80.8% 155U; 83.6% 156-195U; 90% 195U). Treatment-emergent adverse events (TEAEs) were reported in 18/68(26.5%) patients in 155U-group, 41/65(63.1%) in 156-195U-group and 10/13(76.9%) in 195U-group; treatment-related TEAEs were 9(13.2%), 10(15.4%) and 3(23.1%) respectively; serious TEAEs were 0, 3(4.6%) and 1(7.7%), none treatment-related. Conclusions: Long-term treatment with 155U, 156-195U, and 195U-onabotulinumtoxinA in PREDICT was safe and effective CM treatment. No new safety signals were identified.